2007
DOI: 10.1074/jbc.m609875200
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Stimulates Ca2+ Influx and Insulin Secretion in 2-Week-old β-Cells Lacking ATP-sensitive K+ Channels

Abstract: Fine control of insulin secretion by pancreatic ␤-cells is critical for glucose homeostasis: excessive release causes hypoglycemia, whereas insufficient insulin leads to diabetes. Glucose exerts its control on ␤-cells via two major, hierarchical signaling pathways (1). The triggering pathway requires functional ATP-sensitive K ϩ channels (K ATP channels) 2 to produce the essential rise in cytosolic Ca 2ϩ concentration ([Ca 2ϩ ] c ) through the following sequence of events. When the glucose concentration incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
46
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 54 publications
6
46
0
1
Order By: Relevance
“…K ATP channels are not the sole mechanism for the regulation of these complex processes, however. Glucose still induces electrical activity and insulin secretion even when K ATP channels are inactivated (24,25,35,36). Chloride levels in β cells are known to be important for insulin secretion, and chloride channel(s) have been proposed as part of the background channels contributing to the regulation of electrical activity and insulin secretion in β cells, although the identity of such a channel remains elusive (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…K ATP channels are not the sole mechanism for the regulation of these complex processes, however. Glucose still induces electrical activity and insulin secretion even when K ATP channels are inactivated (24,25,35,36). Chloride levels in β cells are known to be important for insulin secretion, and chloride channel(s) have been proposed as part of the background channels contributing to the regulation of electrical activity and insulin secretion in β cells, although the identity of such a channel remains elusive (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…It is this depolarization that raises [Ca 2+ ] i and triggers secretion by opening voltage-dependent Ca 2+ channels (see below). However, there may be additional mechanisms contributing to depolarization, since glucose can still stimulate some voltagedependent Ca 2+ entry in β-cells lacking functional K ATP channels (Szollosi et al, 2007).…”
Section: Role Of Metabolism For Glucose-induced Insulin Secretionmentioning
confidence: 99%
“…The situation is further complicated by the fact that Ca 2+ stimulates metabolism by activating mitochondrial dehydrogenases (McCormack et al, 1990;Civelek et al, 1996;Pitter et al, 2002) and that Ca 2+ may regulate glycolytic enzymes (Jung et al, 2000). Metabolic oscillations may indeed reflect intrinsic oscillatory mechanisms in glucose metabolism, but the oscillations are modified both by stimulatory and inhibitory feedback effects of Ca 2+ (Luciani et al, 2006;Bertram et al, 2007b (Henquin, 2000) or after knocking out functional K ATP channels (Nenquin et al, 2004;Szollosi et al, 2007). This K ATP channel-independent process is mostly considered as an amplification mechanism, which remains functionally silent unless [Ca 2+ ] i is elevated.…”
Section: Role Of Metabolism For Glucose-induced Insulin Secretionmentioning
confidence: 99%
“…Regarding molecular mechanisms, it has been shown that dietary Ca 2þ may lower the activity of the reninangiotensin system (94) and inhibit vascular smooth muscle cell constriction (95) . Besides, Ca 2þ facilitates weight loss (96) and stimulates insulin sensitivity (97) , which contribute to decreases in blood pressure. It remains unclear whether the Ca 2þ content alone or in combination with several components such as other minerals or proteins, peptides or amino acids are responsible for the anti-hypertensive effects of dairy products (96) .…”
Section: Relationship Between Dietary Ca 21 and Lipid Metabolismmentioning
confidence: 99%